2′,4′-dihydroxychalcone alleviates inflammatory bowel disease by inhibiting NLRP3 inflammasome and modulating gut microbiota - Zhang, Guohui; Yao, Yixin; Zhang, Zhongyu; Wang, Jingqi; Xiao, Jian; Yu, Hua; Huang, Mingqing; Yao, Chun; Wang, Yitao; Luo, Hua (Frontiers in Immunology, 2026)
IntroductionAbrus cantoniensis Hance (ACH), an edible traditional Chinese medicinal herb, has significant anti-inflammatory activity. However, there is limited research on the molecular targets of its active ingredients and their application in inflammatory bowel disease (IBD). Nucleotide-binding domain and leucine-rich repeat protein 3 (NLRP3) inflammasome plays a crucial role in IBD.MethodsHere, we explored the inhibitory activity of the 25 main ingredients from ACH on NLRP3 inflammasome using THP-1 and J774A.1 macrophage models, and the dextran sulfate sodium salt (DSS)-induced acute ulcerative colitis mouse model was used to investigate the therapeutic potential. 16S rRNA analysis was performed for gut microbiota assessment.ResultsThe results demonstrated that 2′,4′-dihydroxychalcone (2′,4′-DHC) exhibited the remarkable inhibitory effect on the activation of NLRP3 inflammasome. ELISA and western blotting analyses revealed that 2′,4′-DHC effectively inhibited caspase-1 and Gasdermin D activation and IL-1β release but not TNF-α in macrophages. Furthermore, 2′,4′-DHC significantly alleviated inflammation in IBD mice, which mitigated body weight loss, reduced DAI score, preserved colon length and protected the gut barrier by enhance the tight junction proteins occludin and ZO-1 expression. Importantly, 2′,4′-DHC treatment inhibited NLRP3 inflammasome, while also balancing gut microbiota in colitis mice. The results showed that 2′,4′-DHC reduced the abundance of Proteobacteria, reshaped the bacterial diversity and composition.DiscussionOverall, this study identified 2′,4′-DHC in ACH that regulated the NLRP3 inflammasome activation to exert anti-inflammatory effects in IBD, highlighting its potential in treating NLRP3-related inflammatory diseases.